PENGEMBANGAN MODUL PEMBELAJARAN BERBASIS INKUIRI TERBIMBING UNTUK MENINGKATKAN KETERAMPILAN PROSES SAINS PESERTA DIDIK - Nurfausiah; Sidin Ali; Helmi (Postgraduate, University of Mataram, 2025)
A research on the development of a Guided Inquiry-Based Learning Module for Students of MAS Ummul Mukminin 'Aisyiyah in South Sulawesi Region has been conducted. This study aims to: produce a guided inquiry-based learning module to improve students' science process skills theoretically; produce a guided inquiry-based learning module to improve students' science process skills empirically; describe the effectiveness of using a guided inquiry-based learning module to improve students' science process skills. The research method used is the Research and Development (R&D) method with the 4 D model. The results of the study indicate that the guided inquiry-based learning module developed based on theoretical and empirical validity is recommended for use. The results of the analysis of practitioner responses to the guided inquiry-based learning module developed, obtained an average score of 131.67 which indicates positive criteria. The effectiveness of the guided inquiry-based learning module is seen from the science process skills using the guided inquiry-based learning module and analyzed for the dependent sample t test. The t table value for db = 30 and a significance level of 0.05 is 2.04 so that the t0 value (calculated) = 3.64 or H0 is rejected.